Schistosomiasis and soil-transmitted helminthiasis prevalence and associated factors among school children in the Hawela Tula sub-city, Ethiopia: a cross-sectional study - Wube, Addisalem; Alemu, Tsegaye; Solomon, Tarekegn (Frontiers in Epidemiology, 2025)
BackgroundIntestinal helminthiasis is a neglected tropical disease that affects more than 1.5 billion people worldwide, and school-aged children are particularly vulnerable. However, there is limited local evidence in Hawela Tula sub city.ObjectivesTo identify prevalence and factors associated with Schistosomiasis and Soil-Transmitted Helminthiasis among schoolchildren at the Primary School in Hawassa, Hawela Tula sub city, Sidama Region, Ethiopia.MethodsA school-based cross-sectional study was conducted from October 1 to November 30, 2023. The study used a multistage random sampling technique to select 740 participants. The data were collected via face-to-face interviews using the Kobo collection tool with a smartphone. Stool samples were collected from students and then processed and examined using direct wet mount microscopy and formol-ether concentration techniques. The data were checked for completeness and consistency and then coded and entered into SPSS Version.27, for analysis. Descriptive statistics were computed to describe the data. Bivariate and multivariate logistic regression models were used to assess factors associated with intestinal helminthic infections.ResultsA total of 726 study respondents were included, yielding in a response rate of 98.1%. The mean (±SD) age of the study participants was 8.8 (±2.1) years. The overall prevalence of intestinal helminthic infections among school children was 39.5% (95% CI: 36.0–43.1). The major identified intestinal helminthic parasite species were Ascaris lumbricoides (43.9%), Schistosoma mansoni (26.1%), hookworm species (8.7%), multiple infections (8.7%), and Trichuris trichuria (8.4%). After adjusting for covariates, being in lower grade (1–2) (AOR = 1.53, 95% CI: 1.12–2.10), having a mother with no formal education (AOR = 1.50, 95% CI: 1.05–2.15), having untrimmed fingernails and not clean (AOR = 1.84, 95% CI: 1.12–3.01), not washing hands before meals (AOR = 1.90, 95% CI: 1.35–2.68) and eating unwashed vegetables (AOR = 1.58, 95% CI: 1.11–2.24) were significantly associated with intestinal helminthic infection.ConclusionThis study revealed that four out of ten schoolchildren were infected with intestinal helminthiasis. Children in lower grades born to mothers with no formal education, with untrimmed fingernails and poor hygiene, not practising hand washing before meals, and consuming raw meat and unwashed vegetables were found to be more susceptible to intestinal helminthic infection. To address soil transmitted helminthiasis and Schistosomasis diseases effectively, local governments, regional health bureaus, and development partners should prioritize targeted interventions and implement innovative strategies to reduce their burden. At the community level, schools and families can play a critical role by reinforcing proper hygiene and sanitation practices among children to tackle diseases.